E.Encyclopedia - Penguin Books Ltd (London Penguin Books Ltd, 2003)
The "e.encyclopedia" is the result of collaboration between DK and Google. You can look up a subject of interest in the book, then when directed you can go online to discover a wealth of further information and key facts plus suggestions for further reading. Nine thematic sections in the encyclopedia, including space, earth, history and the human body, cover over 600 subjects and contain links to over 1000 vetted sites that include sound buttons, virtual tours and live footage
Include Color Illustration and Index
Keywords: Leksika -- Informationssøgning